The potential for locating hydrocarbon traps in the Rotliegend formation, based on the results of experimental seismic surveys - Maćkowski, Tomasz; Kwolek, Krzysztof; Górecki, Wojciech (Geology, Geophysics and Environment, 2018)
Within the framework of the Operational Programme Innovative Economy 2007-2013, studies were carried out for improving the effectiveness of using seismic surveys in the prospecting and exploration of gas fields in the Rotliegend formation. The completed experimental seismic surveys provided new, very interesting data on the geological structure of the deeper part of the Rotliegend basin (>4000 m), which is practically very important for prospecting for new gas fields. The interesting results were obtained along virtually the entire cross-section, particularly in two segments: the southern segment – in front of and within the Człopa-Szamotuły tectonic zone (the Szczecin-Gorzów segment) and the northern segment – in the area of the Zabartowo-1 and Zabartowo-2 wells (the Pomeranian segment). In the northern segment, for the first time in the history of studies of the Lower Permian Basin, it was possible to record reflections from the horizon of the aeolian sandstones occurring within the playa silty-clayey deposits (543 m below the top of the Rotliegend formation), which represents a significant achievement from the point of view of prospecting for hydrocarbon resources. This horizon, characterized by favourable reservoir properties, pinches out northward. It is a very important piece of information because systems of lithologic traps may be related to such pinchouts. In the central part of the Obrzycko-Zabartowo profile, in the Chodzież area, a vast structural elevation occurs, approximately 10–12 km wide and with the amplitude of 250–300 m, which may be a potential large structural or structural and lithologic trap. These newly discovered zones of occurrence of gas traps in the seismic profiles made by the AGH University of Science and Technology within the framework of the research project, will be implemented in a detailed seismic exploration during the exploratory work of Polish Oil and Gas Company (PGNiG SA).